Design Of Stock Taking Policy To Reduce The Total Cost Of Stock Taking Using Cycle Counting Method In West Java Distribution Center Of Pt. Xyz - Decky Ridho Sahertian; Dida Diah Damayanti; Budi Santosa (eProceedings of Engineering, 2015)
Abstract PT. XYZ is a 3rd Party Logistic who provide services to the client including Warehousing, Transportation & Distribution, Cross Docking In-plant Value Added Service and Logistics. They have a Distribution Center (DC) in Cibiru, Bandung to handle FMCG product. In maintaining the accuracy of its products, PT. XYZ has an average inventory accuracy for 6 months by 92.71% with the implementation of stock take activity conducted every month to 6 SKU’s calculation. The total of stock take cost is Rp 62.022.000,00, with performing 2 days freeze activity. PT. XYZ needs to redesign the stock take policy and procedure in order to minimize the total cost of stock take activity and improve inventory record accuracy (IRA) higher than 92%. The calculation of ABC cycle counting method is done to determine the number of SKUs are counted in each stock take activity based on the value of each product. Results of calculation ABC cycle counting method is used to determine the schedule of stock take activity. Then the analysis of business process with business process improvement using streamlining tools in order to get an improvement of shorter cycle time. The use of cycle counting method chosen to focus more on calculations based on products that have demand and value. The implementation of the proposed stock take policy can reduce labor time by minimizing the stock take activities up to 19%, and have a load calculation of SKUs quantity reduced by 98.36%. Provide cost reduction of stock take activities as much as 17.30%, by reducing a cost of Rp 10.764.000,00 and The company should not do the freeze activity anymore. Business processes of stock take activities that have increased efficiency of 0.14 and a decreased time in each SKU stock take time of 634.46 seconds to 441.53 seconds. Keywords: 3 PL, Inventory Record Accuracy, Cycle Counting Method, Stock Take Policy, Business Process Improvement, Stock Take Cost